PENGARUH EKSTRAK DAUN Sonneratia alba TERHADAP INFEKSI BAKTERI Aeromonas hydrophila PADA IKAN NILA The Effect of Sonneratia alba Leaf Extract on Aeromonas hydrophila Bacterial Infection in Tilapia - Dumaria R. M. L Tobing; Yunasfi Djayus; Nurmatias Nurmatias (AQUACOASTMARINE, 2017)
Motile Aeromonas Septicemia (MAS) is a disease that attacks on the tilapia fish farming, both in the phase of seed and adult. One of alternative to prevent disease by using the extracts from mangrove plants. The aims of this study was to determine the effectiveness of Sonneratia alba leaf extract in tackling MAS disease in Nila fish and to determine the dose of S. alba extract on Tilapia fish. The extraction from S. alba leaves was made into powder form and then combined with artificial feed type FF-999. The LD50 test was performed on Nila fish for 24 hours. This study used Completely Randomized Design with four treatments: P0 (without of extract S. alba), P1 (1% extract S. alba), P2 (2% extract S. alba), P3 (3% extract S. alba). The results showed that the treatment of P1 and P2 could inhibit the growth of A. hydrophila.Keywords : Sonneratia alba, Tilapia, Antimicrobial Activity, Aeromonas hydrophila.